The 2-good-neighbor connectivity of wheel graph networks - Feng, Wei; Ren, Jiamin; Enhe, Chaolumeng; Jirimutu; Wang, Shiying (Utilitas Mathematica, 2020)
Connectivity is an important measurement for the fault tolerant in interconnection network. A new measure for fault diagnosis of the system is called the ^-good-neighbor connectivity is proposed. A fault set F C V is called a j-good-neighbor faulty set if (v) 0 (V)| > g for every vertex v in V. A ^-good-neighbor cut of a graph G is a g-good-neighbor faulty set F such that G-F is disconnected. The minimum cardinality of ^-good-neighbor cuts is said to be the ^-good-neighbor connectivity of G, denoted by As a famous topol ogy structure of interconnection networks, the n-dimensional wheel graph network CWn has many good properties. In this paper, we prove that the 2-good-neighbor connectivity of CWn is 8n - 18 for n > 5. © 2020 Utilitas Mathematica Publishing Inc.. All rights reserved.